The Overexcited Body : Arte e sport nella societa contemporanea. - Comune di Milano (Genève : Art for The World, 2001)
Acconci, Vito ; Amorales, Carlos ; Arteaparte ; Avveduti, Sergia ; De Barros, Lenora & Campos, Cid ; Delvoye, Wim ; Di Bello, Paola ; Fleury, Sylvie ; Groisman, Michel ; Gursky, Andreas ; Gygi, Fabrice ; Haring, Keith ; Hernández-Diez, José A. ; Hirakawa, Noritoshi ; Kosuth, Joseph ; Kozaris, Dimitris ; Kruger, Barbara ; Leirner, Nelson ; Linke, Armin ; etc.
+ CD : The Overexcited Body: Noritoshi Hirakawa, The Meditation of Insight, 2001, Lenora De Barros & Cid Campos, (Des)Encorpa (The Body Doesn't Mind), 2001, Vito Acconci, Running Tape, 1969
The Overexcited Body : Arte e sport nella societa contemporanea, Velodromo Vigorelli, Milano, 14.3.2001 ; Office des Nations Unives, Genève, 21.3.2001 ; Palazzo dell'Arengario, Milano, 30.3. - 13.5.2001 ; SESC Pompeia, São Paulo, 10 - 12.2001 ; Hôpitaux Universitaires de Genève, 2 - 5.2002 ; Queens Museum, New York, 6 - 10.2002
boek